Anatomy of somatic embryogenesis in Carica papaya L. - Fernando,Juliana A. (2001)
Mature zygotic embryos of Carica papaya L. Sunrise Solo were used as explants for embryogenesis induction. The explants were inoculated on Murashige and Skoog culture medium supplemented with 2 mg.L-1 2,4-dichlorophenoxyacetic acid and incubated in darkness at 25+2°C. Histological analysis of callogenesis and somatic embryogenesis indicated occurrence of direct and indirect somatic embryogenesis development. Direct somatic embryo formation was observed from hypocotyledonary epidermic cells only from explant 18 days after inoculation. Somatic embryos formed indirectly were originated from embryogenic superficial cells of pre-embryonic complexes located on peripherical and on internal cell layers of callus 49 days after inoculation. Diverse morphological differences including disformed embryos were observed among the somatic embryos.